WESBROOK AND HIS UNIVERSITY (Author: William C. Gibson) - Bruneau, William A. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1974)
William C. Gibson. WESBROOK AND HIS UNIVERSITY. Vancouver: The Library, Univ. of British Columbia, 1973. xii + 204 pp. 7.00.